142k views
1 vote
55 points.
Please simplify it .
Don't answer of your don't know.


55 points. Please simplify it . Don't answer of your don't know. ​-example-1
User Tkahn
by
5.5k points

2 Answers

2 votes

Answer:

( i )
\boxed{1}

( ii )
\boxed{2^(6n - 3m - 2)* 3^(3 - m)}

.

Explanation:

( Part i )


\left((1)/(x^(a - b)) \right)^(a + b)\left((1)/(x^(b + a)) \right)^(b - a)


= \left((1)/(x^((a - b)(a + b))) \right)\left((1)/(x^((b + a)(b - a))) \right)


= \left((1)/(x^(a^2 - b^2)) \right)\left((1)/(x^(b^2-a^2)) \right)


= (1)/(x^(a^2 - b^2 + (b^2 - a^2)))


= (1)/(x^0)


= (1)/(1)


= \boxed{1}

.

( Part ii )


(2^(m + n)* 3^(2m + 3) * 4^(2n -1))/(6^(2m + n)* 12^(m - n))


=(2^(m + n)* 3^(2m + 3) * 2^(2(2n -1)))/((2*3)^(2m + n)* (3* 2^2)^(m - n))


=(2^(m + n)* 3^(2m + 3) * 2^(4n -2))/(2^(2m + n)*3^(2m + n)* 3^(m - n)* 2^(2(m - n)))


=(2^(m + n + 4n - 2)* 3^(2m + 3))/(2^(2m + n + 2m - 2n)*3^(2m + n + m - n))


=(2^(m + 5n - 2)* 3^(2m + 3))/(2^(4m - n)*3^(3m))


= 2^(m + 5n - 2 - (4m - n))*3^(2m + 3 - 3m)


= \boxed{2^(6n - 3m - 2)* 3^(3 - m)}

.

Happy to help :)

User Jzou
by
6.2k points
1 vote

Explanation:

i) answer =1

ii) 2 -3m + 6n -2 x 3 3-m

User Eugene Lopatkin
by
5.9k points